Modafinil Trial in Attention Deficit Hyperactivity Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
A film-coated tablet formulation of modafinil (ProvigilR) was used to treat a total of 246 patients, ages 6 to 17 years, with attention deficit hyperactivity disorder (ADHD) at the Massachusetts General Hospital, Boston, MA, and other centers.